Prediction of initiation and total life in fretting fatigue considering kinked cracks. (June 2022) - Rangel, Danilo; Erena, Diego; Vázquez, Jesús; Araújo, J.A.
Highlights: Fretting fatigue model combining initiation and propagation crack stages. Crack initiation length is determined by the size of the critical process fatigue zone. Crack initiation size is obtained iteratively as function of crack initiation life. Abstract: This work proposes a methodology to compute fretting fatigue crack initiation and total life by iterative models calibrated with fatigue stress–strain-life curves. One of the main novelty of such models is the assumption that the crack initiation length is determined by the size of the critical distance. To separate initiation and propagation lives, a numerical approach with finite elements is used. The methodology incorporates not only the multiaxial non-proportional characteristic of the stress field in fretting problems, but also the stress gradient effect. Crack initiation path is obtained by means of the SWT parameter, and to validate it, the analysed results are compared with tests considering a cylindrical-flat configuration (Aluminium 7075-T651 alloy). Most of the life initiation estimates, as well as the total life ones, are within a scatter band of 3.